Performance of FTH-PPM multiple access technology in 60 GHz wireless communication system - Chen SHEN; Xuehua LI (Dianxin kexue)
Aiming at the problem of multiple access interference in 60 GHz pulse wireless communication system,the performance of system based on FTH-PPM multiple access scheme was studied.Under the IEEE 802.15.3.c channel model,the relationship between the bit error rate performance of the system and the number of frequency hopping codes,the signal to noise ratio and the number of users were analyzed.The characteristics of FTH-PPM multiple access modulation system were studied and compared with TH-PPM and TH-PAM schemes.The simulation results show that the system can meet the required bit error rate by changing the signal to noise ratio,the number of hops and the number of users.At the same time,the BER performance of FTH-PPM is better than that of TH-PAM and TH-PPM.The system can select the appropriate multiple access modulation mode according to the value of the pulse duty cycle.The research will provide technical reference for the application of 60 GHz pulse wireless communication.